2020
DOI: 10.3390/coatings10040311
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Microstructure at the Surface of 40CrNiMo7 Steel Treated by High-Current Pulsed Electron Beam

Abstract: High current pulsed electron beam (HCPEB) has recently been developed as an effective technique of material surface modification. In this research, a self-developed HCPEB equipment (HOPE-I) was adopted to perform surface modification on quenched and tempered 40CrNiMo7 steel. A composite nanometer structure was formed on the modified surface layer, and the martensite transformation and the dissolution and fracture of cementite can be observed. After initial irradiation, the high cooling rate caused the formatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 23 publications
(23 reference statements)
0
5
0
Order By: Relevance
“…The surface structure and properties of the materials can be modified by a number of methods, including the deposition of thin films [6,7], ion implantation [8], modification by high energy fluxes (such as electron [9,10] or laser beam [11]), etc. Currently, the electronbeam surface treatment technologies for surface treatment and modification, which are a part of additive manufacturing technologies for surface modification, receive a lot of attention and are considered very promising due to the possibility of the precise control of the technological conditions, structure, and functional properties of the modified materials [12].…”
Section: Introductionmentioning
confidence: 99%
“…The surface structure and properties of the materials can be modified by a number of methods, including the deposition of thin films [6,7], ion implantation [8], modification by high energy fluxes (such as electron [9,10] or laser beam [11]), etc. Currently, the electronbeam surface treatment technologies for surface treatment and modification, which are a part of additive manufacturing technologies for surface modification, receive a lot of attention and are considered very promising due to the possibility of the precise control of the technological conditions, structure, and functional properties of the modified materials [12].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Wei et al [7] applied electron-beam surface modification of 5CrMoMn steel and concluded that the surface roughness, wear-resistance, and microhardness were significantly improved. The authors of [8] demonstrated that the corrosion resistance of 40CrNiMo7 steel was enhanced after surface modification by an electron beam. Currently, combinations of several methods for surface treatment, including electron-beam modification, thin films deposition, plasma nitriding etc.…”
Section: Introductionmentioning
confidence: 99%
“…A high-current pulsed electron beam has proven to be an effective tool for the microstructural modification of steels [28,29], Al-Mg [30], and Ni alloys [31]. However, only a few studies have been devoted to surface modification of HEAs by HCPEB.…”
Section: Introductionmentioning
confidence: 99%